The Effect of Incentive Policy on Manufacturer’s Disruption Recovery In Building A Resilient Supply Chain - Liu, Naimeng; Liu, Bin; Yun, Qiaoyun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
The outbreak of the epidemic and the complex international situation have caused supply disruptions to varying degrees. To survive the disruption, it is critical to think about how to build a resilient supply chain. We examine the manufacturer’s recovery capacity under the fiscal interest-discount rate and tax discount rate. Motivated by the current incentive policies, such as the fiscal interest-discount policy and tax preference policy, we develop a game-theoretical game model focusing on a manufacturer aiming to maximize profits, a government aiming to maximize utility, and consumers. We have derived optimal decisions for products with varying degrees of scarcity after disruption by analyzing the perspectives of profit maximization and social welfare optimization for each entity in the supply chain. We find that for the recovery of moderately scarce products, the fiscal interest-discount policy will be the optimal choice for both the interrupted manufacturer and the government. However, as production scarcity increases, the manufacturer will prefer the tax preference policy.